INTEGRATING NONVERBAL LINGUOCULTURAL COMPETENCE IN HIGHER EDUCATION: A RESOURCE-BASED APPROACH TO 20TH-CENTURY UZBEK AND ENGLISH FICTION - Yoqubova Sevinch Vosidjon qizi (TRANSMILLIY QO‘SHMA TA’LIM DASTURLARINING RIVOJLANISHI: O‘ZDJTU TAJRIBASI VA XALQARO SIFAT KAFOLATI TIZIMLARI BO‘YICHA ILMIY-AMALIY YONDASHUVLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Since the Uzbekistan higher education system is oriented toward the international accreditation standards, the Quality Assurance (QA) frameworks, the definition of the so-called communicative competence is also changing. Contemporary pedagogical frameworks frequently emphasise verbal fluency, thereby overlooking the "silent language" of nonverbal communication. This paper suggests a shift to Competency-Based Education (CBE) that regards nonverbal linguoculturology as an assessable skill. Utilising a comparative analysis of 20th-century Uzbek and English fiction, we delineate culturally specific indicators of kinesics and proxemics. We advocate for the establishment of curated nonverbal datasets to facilitate academic mobility and intercultural literacy, drawing on the "Resource Families" model employed in European research infrastructures.